Late‐onset retinal degeneration pathology due to mutations in CTRP5 is mediated through HTRA1. Issue 6 (5th August 2019) - Chekuri, Anil; Zientara‐Rytter, Katarzyna; Soto‐Hermida, Angel; Borooah, Shyamanga; Voronchikhina, Marina; Biswas, Pooja; Kumar, Virender; Goodsell, David; Hayward, Caroline; Shaw, Peter; Stanton, Chloe; Garland, Donita; et al.
Abstract: Late‐onset retinal degeneration (L‐ORD) is an autosomal dominant macular degeneration characterized by the formation of sub‐retinal pigment epithelium (RPE) deposits and neuroretinal atrophy. L‐ORD results from mutations in the C1q‐tumor necrosis factor‐5 protein (CTRP5), encoded by the CTRP5/C1QTNF5 gene . To understand the mechanism underlying L‐ORD pathology, we used a human cDNA library yeast two‐hybrid screen to identify interacting partners of CTRP5. Additionally, we analyzed the Bruch's membrane/choroid (BM‐Ch) from wild‐type ( Wt ), heterozygous S163R Ctrp5 mutation knock‐in ( Ctrp5 S163R/wt ), and homozygous knock‐in (Ctrp5 S163R/S163R ) mice using mass spectrometry. Both approaches showed an association between CTRP5 and HTRA1 via its C‐terminal PDZ‐binding motif, stimulation of the HTRA1 protease activity by CTRP5, and CTRP5 serving as an HTRA1 substrate. The S163R‐CTRP5 protein also binds to HTRA1 but is resistant to HTRA1‐mediated cleavage. Immunohistochemistry and proteomic analysis showed significant accumulation of CTRP5 and HTRA1 in BM‐Ch of Ctrp5 S163R/S163R and Ctrp5 S163R/wt mice compared with Wt . Additional extracellular matrix (ECM) components that are HTRA1 substrates also accumulated in these mice. These results implicate HTRA1 and its interaction with CTRP5 in L‐ORD pathology. Abstract : The S163R mutation in C1q‐tumor necrosis factor‐5 protein (S163R‐CTRP5) results in accumulation of drusen‐like deposits containing HTRA1 serine protease and CTRP5 in the Bruch's membrane/choroid (BM‐Ch) which lead to L‐ORD in patients. Both WT and S163R‐CTRP5 bind HTRA1. While WT‐CTRP5 stimulates the HTRA1 protease activity and serves as its substrate, S163R‐CTRP5 is resistant to HTRA1‐mediated cleavage. Accumulation of HTRA1 and cleavage‐resistant S163R‐CTRP5 may result in the formation of pathological deposits rich in these two proteins in BM‐Ch.